ISSUES OF THE RELATIONSHIP OF LANGUAGE AND CULTURE IN LINGUOCULTUROLOGY - G.I. Akramova (Galaxy International Interdisciplinary Research Journal, 2022)
The article covers the issues of correlation between language and culture, considers the problems of linguoculturology as a science, its national and cultural specificity, as well as the role of the text as a cultural unit.